PENERAPAN EDUKASI GIZI DAN KELAS MEMASAK BAGI IBU SISWA PAUD DI KECAMATAN CIMAHI UTARA KOTA CIMAHI - Maryati Dewi; Yenny Moviana; Witri Priawantiputri (Poltekkes Kemenkes Bandung, 2022)
One of the reasons for the emergence of nutritional problems in the community is the non-implementation of balanced nutrition messages. Early childhood nutrition education can affect nutritional status later in life. For this reason, it was necessary to carry out nutrition education as early as possible to comprehend balanced nutrition for mothers. Several studies have shown that nutrition education programs combined with cooking classes can increase understanding of healthy eating.This community services aimed to increase the comprehension of healthy and nutritious food in pre-primary school mother's in the Cimahi city, through nutrition education and cooking classes for pre-primary school students. The target is the mother of pre-primary school students and pre-primary school students of the PAUD Qurrota Aina and the PAUD Daarul Ikhlas of Cimahi city. The activity applied in community service was the preparation, implementation (nutrition education and cooking class), and evaluation (a food menu creation competition and healthy balanced nutritious snacks for children). The activity implemented by Lecturers of Jurusan Gizi Poltekkes Kemenkes Bandung assisted by students of Jurusan Gizi. As result, there was an increase in knowledge of balanced nutrition, choosing safe foods and skills in preparing a balanced healthy menu for mothers of PAUD students. This activity also increases the type of fruits and vegetables consumed by PAUD students.